PENGARUH PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN MATEMATIS SISWA (DITINJAU DARI KEMAMPUAN REPRESENTASI DAN KOMUNIKASI) - Hidayatul Purnama Ariyanti (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
This research is motivated by the low mathematical ability of students seen in the test results Programme for International Student Assessment (PISA) in 2012. The ability of mathematics not only be based on the ability of understanding only, but there are also other capabilities that factor into the level of mathematical ability of students, among others, representation and communication capabilities. So to overcome this use realistic mathematics learning. Formulation of the problem in this research is "Is there any realistic mathematics education effect on the ability of students' mathematical representation and communication?". The goal was to determine the effect of realistic mathematics learning of the mathematical ability of students' representation and communication. The method used is Posttest-Only Control Design which will give treatment to the realistic mathematics learning experiment class and conventional learning to control class. After treatment, given posttes to measure its influence in the ability of students' mathematical representation and communication. The research instrument in the form of tests which contains the indicator variables. Subjects in this study were 32 students of the control class and 32 students for the experimental class. For data analysis used the t-test previously conducted pre-requisite test the normality and homogeneity test. In this study, H0 reads No realistic mathematics education effect on the ability of students' mathematical representation and communication. And H1 reads no realistic mathematics education effect on the ability of students' mathematical representation and communication. The results show the ability of the student representation is obtained and the communication skills of students obtained which showed that H0 refused on both. It can be concluded that the realistic mathematics instruction affect the ability of students' mathematical representation and communication. Keywords: Realistic Mathematics Education, Communication Skills, Representation Skills.